The collected letters of A. W. N. Pugin - Pugin, Augustus Welby Northmore, 1812-1852; Belcher, Margaret (Oxford : Oxford University Press, 2001)
"The importance of A. W. N. Pugin (1812-52) in the history of the Gothic Revival, in the development of ecclesiology, in the origins of the Arts and Crafts Movement, and in architectural theory is incontestable. A leading British architect who was also a designer of furniture, textiles, stained glass, metalwork, and ceramics, he is one of the most significant figures of the mid-nineteenth century and one of the greatest designers. His correspondence is important because it provides more insight into the man and more information about his work than any other source. In this volume, the third of five, which spans the years 1846 to 1848, Pugin's two most important churches are completed and the first part of the House of Lords is opened. He makes his only trip to Italy, and he marries for the third time. His correspondence sheds light too on the religious life of the time, especially ecclesiastical politics." --Book Jacket.
v. 1. 1830-1842 -- v. 2. 1843-1845 -- v. 3. 1846-1848 -- v. 4. 1849 to 1850 -- v. 5 1851 to 1852
Volume 1 ©2001 reprinted 2008; volume 2 ©2003 reprinted 2007; volume 3 ©2009 reprinted 2012.
Includes bibliographical references and index.
Keywords: Pugin, Augustus Welby Northmore, -- 1812-1852 -- Correspondence; Architects -- England -- Correspondence; England -- Religious life and customs -- 19th century